1990
DOI: 10.1056/nejm199012063232305
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Immunotherapy with Venom in Children with Allergy to Insect Stings

Abstract: These data confirm that immunotherapy with insect venom prevents recurrences of systemic reactions after subsequent insect stings. Because of the surprisingly low rate of reactions among untreated children, we could not identify any characteristics that were predictive of repeat reactions. Since only 9.2 percent of stings in the untreated children led to a systemic reaction and since there was no progression to a more severe reaction, we conclude that venom immunotherapy is unnecessary for most children who ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
7

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(122 citation statements)
references
References 13 publications
3
112
0
7
Order By: Relevance
“…In the third selected study, Valentine et al 9 performed a trial similar to the previous one, among children who presented reactions restricted 7 Schuberth et al 8 Valentine et al 9 Brown et al 10 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the third selected study, Valentine et al 9 performed a trial similar to the previous one, among children who presented reactions restricted 7 Schuberth et al 8 Valentine et al 9 Brown et al 10 …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, the study by Schuberth et al 8 (1983) showed an OR for systemic reactions after accidental stings of 0.35 (0.05 < OR < 2.56), while the study by Valentine et al 9 showed a calculated OR of 0.16 (0.02 < OR < 1.21). After meta-analysis on these two studies, the OR became 0.29 (0.10 < OR < 0.87) ( Table 3).…”
Section: Participantsmentioning
confidence: 91%
See 3 more Smart Citations